Implications of Fintech and High Frequency Trading (HFT) Developments on Capital Market Efficiency: A Systematic Literature Review - Annesa Tasya Maghfirah; Mubdi Dzuwhandy; Syarifuddin Syarifuddin; Darmawati Darmawati (West Science Accounting and Finance, 2025)
With the rapid development of digital technology, global capital markets are undergoing a major transformation through the emergence of Financial Technology (FinTech) and High-Frequency Trading (HFT). This study aims to examine how these two technologies affect capital market efficiency in various countries. The method used was a Systematic Literature Review (SLR), examining 27 scientific articles published between 2021 and 2025 relevant to the topics of FinTech, HFT, and market efficiency. The results show that the implementation of FinTech and HFT can increase liquidity, transaction speed, and price efficiency through the use of technologies such as trading algorithms, blockchain, and automated trading systems. However, in developing markets, their impact remains limited due to limited digital infrastructure, immature regulations, and low financial literacy. Therefore, technological readiness, adaptive governance, and strong regulations are critical factors in ensuring stable and sustainable market efficiency. The implications of this study provide new insights into the role of financial technology in strengthening market efficiency and serve as a basis for policymakers and researchers in developing future digital capital markets.